37 Optimization of supercritical carbon dioxide extraction conditions of Semen cassiae volatile oil using response surface methodology and antimicrobial activity detection. (19th December 2016) - Wu, Liyan; Wang, Liying; Jin, Yuanbao; Jin, Yuanyuan; Wang, Yanzhen; Meng, Fanxin
Abstract : Objectives: The objective of this project was to study the process of extracting Semen cassia. The volatile components of Semen cassia were analyzed using supercritical CO2 extraction (SCDE). Based on a single factor experiment, response surface methodology was used to investigate the extraction of volatile oil. According to the fitted curves under different conditions, the effects of pressure, temperature and time on extraction and interactions between various factors were determined. Antimicrobial activity was also measured. Methods: A Box-Behnken central composite design method was used based on single factor experiments. The influence of extraction temperature, extraction time and extraction pressure on extraction yield was studied. The response surface method was employed to analyze the results of experiments. The disk diffusion method was used to detect the antimicrobial activity of Semen cassiae volatile oil. Results: The results indicated that the optimum extraction conditions were as follows: extraction temperature 51°C, extraction time 3.22 hours and extraction pressure 25 MPa. Extraction yield reached 2.34%. The volatile oil of Semen cassiae extracted from the tested strains showed antimicrobial activity, with MIC values ranging from 2.5 to 5 mg/mL. Conclusions: SCDE is a stable and efficient process. Semen cassiae volatile oil had antimicrobial activity which could provide a theoretical basis for application of this oil.